Kontribusi Profitabilitas terhadap Nilai Perusahaan di Indonesia - Revinna Tonay; Julisar Surjadi (Media Bisnis, 2025)
The aim of this research is to analyze the effect of independent variables on dependent variables, such as firm value. The object of this research includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for a three years period from 2021 to 2023. This research uses the purposive sampling method as the sampling method and the multiple regression method to analyze the data. There are 77 companies with a total of 231 data that passed the research criteria. The results of this research show that profitability, liquidity, and capital structure have a positive effect on firm value. High profitability gives investors a positive picture of the company's future prospects. High liquidity indicates efficiency in the use of current assets and fulfillment of short-term obligations. High capital structure indicates that the company is growing and needs more funds, which are obtained through debt. Other independent variables, such as firm size, company growth, activity ratio, capital expenditure and institutional ownership have no effect firm value.